2015
DOI: 10.1093/jxb/erv129
|View full text |Cite
|
Sign up to set email alerts
|

Autumnal leaf senescence inMiscanthus×giganteusand leaf [N] differ by stand age

Abstract: HighlightThis chronosequence field experiment found unexpected differences in leaf senescence symptoms between different aged Miscanthus×giganteus stands, potentially indicating differential senescence with plant age and nutrient status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 31 publications
4
22
0
Order By: Relevance
“…Rhizomes are needed for overwintering, and stored carbohydrate is remobilised to drive spring regrowth in the following year. Biomass and canopy senescence were not found to be correlated with overwinter survival in Miscanthus (Clifton‐Brown & Lewandowski, ); however, stay‐green Miscanthus survived poorly in higher latitudes in Europe (Clifton‐Brown et al., ) and first‐year M × g overwintered poorly in a study in the United States and maintained active leaves after late‐season frosts, suggesting a lack of senescence may be responsible (Boersma, Dohleman, Miguez, & Heaton, ). We anticipate the production of rhizome and the timing of senescence are critical factors in overwinter survival and that this is strongly linked to canopy duration in particular during the first year of establishment.…”
Section: Discussionmentioning
confidence: 99%
“…Rhizomes are needed for overwintering, and stored carbohydrate is remobilised to drive spring regrowth in the following year. Biomass and canopy senescence were not found to be correlated with overwinter survival in Miscanthus (Clifton‐Brown & Lewandowski, ); however, stay‐green Miscanthus survived poorly in higher latitudes in Europe (Clifton‐Brown et al., ) and first‐year M × g overwintered poorly in a study in the United States and maintained active leaves after late‐season frosts, suggesting a lack of senescence may be responsible (Boersma, Dohleman, Miguez, & Heaton, ). We anticipate the production of rhizome and the timing of senescence are critical factors in overwinter survival and that this is strongly linked to canopy duration in particular during the first year of establishment.…”
Section: Discussionmentioning
confidence: 99%
“…Given the long-term and large-scale focus of this study, factors that may increase the DIN leaching such as poor establishment and immaturity of the stand (e.g., Smith et al, 2013) were not considered. The timing of harvest and stand age may also have a significant effect on the N concentrations of biomass (Heaton et al, 2009) and the mass of N removed at harvest (Boersma et al, 2015). In this study, a constant harvest date for miscanthus and switchgrass was used; therefore, the influence of timing of harvest was not accounted for.…”
Section: Discussionmentioning
confidence: 99%
“…For the current analysis, an algorithm was developed and calibrated based on measured data (Himken et al, 1997;Heaton et al, 2009;Dohleman et al, 2012;Wilson et al, 2013;Boersma et al, 2015) to simulate the movement of C and N between aboveground (i.e., shoots) and belowground (i.e., roots and rhizome) pools. Miscanthus and switchgrass each have their own algorithm that is based on the mass balance and tissue-specific N concentration data (Dohleman et al, 2012).…”
Section: Agro-ibis Descriptionmentioning
confidence: 99%
“…Christian and Haase () hypothesized that the first‐year plants of M×g ‘1993–1780' did not go dormant early enough in the season to avoid damage from cold temperatures. Boersma, Dohleman, Miguez, and Heaton () found that when autumn temperature fell below 10°C in Ontario, Canada, CO 2 assimilation rate and photosystem II efficiency for first‐year stands of M×g ‘1993–1780' were almost four times higher than for the third‐year plants, and leaf [N] was about 2.4 times greater, suggesting that the first‐year plants were still actively growing before a killing frost. From this photosynthesis data, Boersma et al () concluded that limited translocation of nutrients to rhizomes in the first‐year plants of M×g ‘1993–1780' contributed to their poorer overwintering ability than the third‐year plants in Ontario, though no measurements of rhizome nutrient contents were made.…”
Section: Introductionmentioning
confidence: 99%
“…Boersma, Dohleman, Miguez, and Heaton () found that when autumn temperature fell below 10°C in Ontario, Canada, CO 2 assimilation rate and photosystem II efficiency for first‐year stands of M×g ‘1993–1780' were almost four times higher than for the third‐year plants, and leaf [N] was about 2.4 times greater, suggesting that the first‐year plants were still actively growing before a killing frost. From this photosynthesis data, Boersma et al () concluded that limited translocation of nutrients to rhizomes in the first‐year plants of M×g ‘1993–1780' contributed to their poorer overwintering ability than the third‐year plants in Ontario, though no measurements of rhizome nutrient contents were made. Genetic variation in Miscanthus for overwintering ability in the establishment year could be due to differences in freeze tolerance of dormant rhizomes, differences among genotypes in timing of dormancy and translocation of nutrients belowground, differences in depth of dormant buds in the soil to facilitate avoidance of freezing temperatures, or combinations of these traits.…”
Section: Introductionmentioning
confidence: 99%